AB1813-HPR PREVALENCE AND EVOLUTION OF OCCUPATIONAL SHOULDER TENDINITIS OVER A PERIOD OF 10 YEARS IN THE TUNISIAN CENTER REGION - Asma, G.; Brahem, A.; Chouchen, A.; Mejri, R.; Kacem, I.; Maoua, M.; El Maalel, O.; Kalboussi, H.; Chatti, S.; Mrizek, N. (Annals of the rheumatic diseases, 2023)
BackgroundShoulder pain is one of the most common regional pain syndromes. Shoulder tendinitis is the second recognized cause of musculoskeletal disorders of the upper limbs after carpal tunnel syndrome. Symptoms can be persistent and disabling in terms of an individual’s ability to carry out daily activities both at home and in the workplace with significant and socio-economic costs.ObjectivesTo assess the prevalence of occupational tendinitis of the shoulder and its evolution during the study period, and to describe the socioprofessional characteristics of the workers.MethodsThis is a retrospective cross-sectional study of all cases of tendonitis of the rotator cuff, working in the private sector, recognized by the competent medical commission of the National Medical Care Fund of the region of Tunisian center over a period of 10 years.ResultsDuring the study period, we identified 635 cases of shoulder tendinitis, i.e. 29.5% of all musculoskeletal disorders of the upper limbs. The average age of the population was 44.56 years ± 7.7 years. Our study population was mainly women (82.5%) with a sex ratio of 0.21. The majority of patients worked in the textile sector (76.2% i.e. n= 487) and the electronic sector (4.5% i.e. n= 28). Average seniority of workers in their jobs was ranging from 1 to 36 years. Seamstress (63.4%) and workman (17.7%) were the most affected jobs. The cases of shoulder tendinitis were in continuous rise over the 10 years (p=0.001, r=0.86).ConclusionOur study add an evidence to suggest that shoulder disorders may be increased among some workers, particularly those with jobs involving combinations of exposure to: overhead work and repetition. Most of the research on management of shoulder disorders has rarely included occupational outcomes. Adequate and rigorous prevention is essential to reduce the prevalence of this with painful consequences.References[1] Ohlsson K, Attewell RG, Johnsson B, et al. An assessment of neck and upper extremity disorders by questionnaire and physical examination. Ergonomics. 1994;37:891–897.[2] Boocock MG, Collier JMK, McNair PJ, et al. A framework for the classification and diagnosis of work-related upper extremity conditions; systematic review. Semin Arth Rheum. 2009;38:289–311.[3] Miranda H, Punnett L, Viikari-Juntura E, et al. Physical work and chronic shoulder disorder. Results of a prospective population-based study. Ann Rheum Dis. 2008;67:218–223.Acknowledgements:NIL.Disclosure of InterestsNone Declared.